PEMANFAATAN HASIL HUTAN BUKAN KAYU (HHBK) PADA RANGKAIAN UPACARA PERNIKAHAN MASYARAKAT DI NAGARI KAYUTANAM KECAMATAN 2X11 KAYUTANAM KABUPATEN PADANG PARIAMAN - Susilastri Susilastri; Desyanti Desyanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine the types of NTFPs and their utilization in a series of community wedding ceremonies in Nagari Kayutanam, 2x11 Kayutanam District, Padang Pariaman Regency. This research was conducted from June to July 2021. The method used in this research is a qualitative method and uses a snowball sampling technique with the help of a structured interview guide. The total number of respondents was 10 respondents, 3 respondents from the Head of Density Adat Nagari and 7 respondents from ordinary people, to find out the use of NTFPs in a series of wedding ceremonies. At the HHBK gathering event, 11 types were used, at the HHBK application event, 6 types were used, 20 types were used at the HHBK wedding event, 22 types were used at the HHBK reception event, and 19 at the bitch-manjalang event. type. The total types of NTFPs identified in the entire series of wedding ceremonies were 22 types of plant NTFPs, namely jengkol (Archidendron pauciflorum), jackfruit (Artocarpus heterophyllus), bamboo/bamboo shoots (Dendrocalamus asper), coconut (Cocos nucifer) aren (Arenga pinnata), cinnamon (Cinnamomum verum), nutmeg (Myristica fragrans), candlenut (Aleurites moluccanus), turmeric (Curcuma longa), ginger (Zingiber officinale), galangal (Alpinia galangal), lemongrass (Cymbopogon citratus), ruku-ruku (Ocimum tenuiflorum), salam (Syzygium polyanthum), pandan (Pandanus amaryllifoliu), coffee (Coffea robusta), tea (Camellia sinensis), areca nut (Areca catechu), betel nut (Piper betle), gambier (Uncaria), frankincense (Styrax benzoin) and tobacco (Nicotiana tabacum). Of the 22 types of NTFPs above, there are 5 types of NTFPs used for cultural rituals, namely areca nut (Areca catechu), betel nut (Piper betle), gambier (Uncaria), frankincense (Styrax benzoin) and tobacco (Nicotiana tabacum) and there are 5 types of NTFPs that are Dominantly used in each series of wedding ceremonies are areca nut (Areca catechu), betel nut (Piper betle), gambier (Uncaria), frankincense (Styrax benzoin) and tobacco (Nicotiana tabacum). The use of NTFPs by the people of Nagari Kayutanam is for making huts, cooking ingredients, processed drinks and for cultural rituals.Keywords: Non-Timber Forest Products ; Culture.